Analisis Pengakuan Akuntansi Sistem Bagi Hasil Atas Pembiayaan Akad Mudharabah Berdasarkan PSAK 105 - Salsa Mey Lenzya; Wirman Wirman (Peneliti.net, 2022)
The purpose of this study is to find out how it works and to identify the accounting recognition of the revenue sharing system for Mudharabah financing at BMT Fajar Bekasi branch, in order to determine whether the accounting recognition for mudharabah financing with Futures Mudharabah Savings products at BMT Fajar is in accordance with PSAK 105 or not. The method used in this study is to use descriptive qualitative research. The type of data used is secondary data, data in the form of articles, as well as scientific writing, journals, research reports, sources that can be obtained from the internet related to this study, as well as library books relevant to this research. The data collection technique was spelled out by using data trigulation which was obtained by observation, interviews and also using literature studies and library research. The analysis used by researchers is deductive analysis.